“This is 1986. This isn’t like the 60s and 50s”: Locating the Long Civil Rights Narrative in Just Mercy (2019) - Johanne Østergaard; Mikkel Jensen (European Journal of American Studies)
Most mainstream films about the civil rights movement are set in the South in the 1950-1960s, but this article points out how Hollywood in the 2010s broke new ground by also portraying civil rights struggles after that era. Many historians have heeded Jacqueline Dowd Hall’s call to revise the American civil rights narrative, and this article argues that Destin Daniel Cretton’s Just Mercy (2019) is a part of a wave of “long civil rights films.” Exploring how Just Mercy portrays a key injustice that continues to affect contemporary America while also showing civil rights activism to continue into the 1980s, 1990s, and onwards, the article argues that Just Mercy’s depiction of the unjust treatment, conviction, and incarceration of Alabama native Walter McMillian in the late 1980s effectively calls for a revised understanding of the longer lines of civil rights activism.